The environment under the knife: A review of current Eco-surgical strategies and recommendations for Pakistan - Seth Martins, Russell; Edward Anthony Joseph; Javeria Tariq; Namrah Aziz; admin; Saulat H. Fatimi (Journal of the Pakistan Medical Association, 2022)
The healthcare sector at its core is based on the fundamentals belief to do no harm and bring about betterment in the lives of the people. Paradoxically, hospitals are one of the leading contributors to pollution, greenhouse gas (GHG) emissions and toxic waste material worldwide. Surgical care delivery is quite resource intensive, consuming significant amount of energy and equipment as well as producing large quantities of waste. With climate change being a global priority, it is crucial that hospitals re-evaluate the environmental impact of such practices. The current review was planned to identify areas of improvement in surgical care in terms of sustainability, as well as describe efficient and innovative strategies for hospitals in Pakistan to lessen their impact on the environment. Continuous...